Paediatric empyema: video-assisted thoracoscopic surgery (vats) and its outcome study - G., Manasa; B., Swetha; T., Yashoda H.; S., Pramod (International Journal of Contemporary Pediatrics, 2017)
Background: Empyema thoracis defined as purulent pleural effusion is a common condition in children with significant morbidity and mortality. The aim of therapy for empyema is to ensure rapid recovery with a normal long term pulmonary outcome. VATS (Video-assisted thoracoscopic surgery) is gaining acceptance as a primary modality of treatment in cases of early empyema. VATS is associated with decreased morbidity and reduced hospital stay of the patient. Methods: This is a retrospective observational study conducted in the department of pediatrics KIMS Hospital, Bengaluru from November 2014 to November 2016. In this study, review of the medical records of all the children aged 2 months to 18 years, who underwent VATS for empyema was done. The children included in the study were diagnosed with empyema thoracis based on chest X- ray, USG chest and CT chest and have undergone VATS by pediatric surgical team. Results: The median age of presentation was 4.1 yrs. 18 children were malnourished of which 3 had severe malnutrition. Male to female ratio was 1:1. Most common symptoms were fever (96%), cough (84%), respiratory distress (61%) and chest pain (48%). All patients had parapneumonic effusions and received antibiotics before undergoing surgery. Post-operative supplemental oxygen was required for 2.5±0.5 days. Chest tubes were removed in 4.53±0.7days and duration of stay in hospital was 8.26±1.77 days. All patients were afebrile before discharge and were discharged on oral antibiotics. Follow-up data showed that symptoms resolved in 24 children, 2 children had complications, one child had a pneumothorax and another had a broncho-pleural fistula. Results: Most common symptoms were fever (96%), cough (84%), respiratory distress (61%) and chest pain (48%). All patients had parapneumonic effusions and received antibiotics before undergoing surgery. Post-operative supplemental oxygen was required for 2.5±0.5 days. Chest tubes were removed in 4.53±0.7days and duration of stay in hospital was 8.26±1.77 days. All patients were afebrile before discharge and were discharged on oral antibiotics. Conclusions: These results suggest that primary operative therapy in the form of VATS is an effective treatment option for children with empyema. VATS is associated with a lower in-hospital mortality rate, re-intervention rate, length of stay and duration of tube thoracostomy.